Language Variations In Madurese across Regions and Age Groups: Looking at Syntactic and Lexical Variations among Regions and Age Groups - Syariful Muttaqin; Sahiruddin Sahiruddin; Iis Nur Rodliyah (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2019)
This research is aimed to describe the syntactic and lexical variations of Madurese language based on different ages and regions in Madura. This is due to the changing phenomena of language especially Madurese due to socioeconomic and technological development. Participants of this study were youths and old groups from different regions. Data were analyzed quantitatively and qualitatively in accordance to the research problems. It was found out that syntactically, Madurese language has similar basic word order structure as Indonesian language. The possessive structure is determined by the last sound of the word, either vocal or consonant. Other structures, noun phrase, prepositions, adjective clause, nonverbal clause, and existential clause are much similar to that of Indonesian language. No differences were found in terms of syntactic variations among different ages and regions in Madura. In terms of lexical, some variations do occur as attributed to the socio-cultural background of each speaker. The level of politeness indicates that social level influences the choice of lexical terms used by speakers based on different ages and regions in Madura.